Program of physical therapeutic activities to improve the physical condition related to health in schools with anemia falciforme (Original) (Revista científica Olimpia, 2019)
The practice of therapeutic physical activities in the care of school children exempted from physical education classes for different diseases is considered a positive and healthy phenomenon, however, we must consider how much is the limit of what is permissible to provide the energy and vitality necessary in Schoolchildren with sickle-cell anemia. For this reason, a program of therapeutic physical activities was developed to improve the physical condition related to health in schoolchildren with sickle cell anemia. The sample consisted of 10 schoolchildren with sickle cell anemia who study in four primary schools in the Bayamo municipality, Granma province. Theoretical, empirical and statistical-mathematical methods were used to guide the investigative process.
Keywords: sickle cell anemia; physical condition; health; therapeutic physical activities